2021
DOI: 10.1021/jacs.1c04378
|View full text |Cite
|
Sign up to set email alerts
|

Stapled β-Hairpins Featuring 4-Mercaptoproline

Abstract: Peptides constrained by intramolecular cross-links, especially stapled α-helices, have emerged as versatile scaffolds for drug development. However, there are fewer examples of similarly constrained scaffolds for other secondary structures. Here, we used a novel computational strategy to identify an optimal staple for antiparallel β-strands, and then we incorporated that staple within a β-hairpin peptide. The hairpin uses 4-mercaptoproline as a novel staple component, which contributes to a unique, kinked stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Based on the dihedral angles of bound Pen3- ortho and Ramachandran plots of proline and pre-proline residues, , we hypothesized that a 4-mercaptoproline (4MP) residue within the staple would favor Pen3- ortho ’s GABARAP-selective binding conformation. 4MP conformationally restricts both the backbone and the staple, and we recently reported its use as a valuable building block for peptide stapling for non-α-helical peptides . Testing a panel of Pen3- ortho analogues with 4MP in the third position (parent peptide MP3), we found that 4MP substitution maintained high GABARAP affinity while decreasing binding affinity to LC3B for all staple geometries (Figure a).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Based on the dihedral angles of bound Pen3- ortho and Ramachandran plots of proline and pre-proline residues, , we hypothesized that a 4-mercaptoproline (4MP) residue within the staple would favor Pen3- ortho ’s GABARAP-selective binding conformation. 4MP conformationally restricts both the backbone and the staple, and we recently reported its use as a valuable building block for peptide stapling for non-α-helical peptides . Testing a panel of Pen3- ortho analogues with 4MP in the third position (parent peptide MP3), we found that 4MP substitution maintained high GABARAP affinity while decreasing binding affinity to LC3B for all staple geometries (Figure a).…”
Section: Resultsmentioning
confidence: 80%
“…Covalent linking of side chains, or “peptide stapling,” is a promising strategy to minimize these limitations . While most stapled peptides are α-helical, we and others have shown that appropriately designed staples can improve the properties of peptides in other conformations as well. , Based on the crystal structure of K1 bound to GABARAP, we designed peptides Cys5, Cys4, and Cys3, which stapled K1 in ( i , i + 3), ( i , i + 4), and ( i , i + 5) positions, respectively (Figure a). We stapled each peptide using dithiol bis-alkylation with ortho- , meta- , and para- dimethylbenzene linkers, allowing for a “diversity-oriented stapling” approach, where the staple geometry was varied (Figure a). ,, Stapling in ( i , i + 3) positions (the Cys5 peptides) reduced binding to both GABARAP and LC3B compared to K1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9], [10] Recently, alternative structural elements, such as βhairpins and loops have been successfully utilised for stapling. [11], [12] Stapling of the nucleophilic side chain of cysteines has been explored as an attractive alternative to RCM, as it avoids the use of non-natural amino acids and metal catalysts. [13] Stapling of cysteines can be done in mild, biocompatible conditions, allowing it to be used in the context of affinity selections of combinatorial libraries.…”
Section: Introductionmentioning
confidence: 99%